Princess in Love - Pasternak, Anna (London Bloomsbury, 1994)
An account of the alleged love affair between Diana, the Princess of Wales, and Major James Hewitt
Include Illustration
Keywords: Great Britain -- Princesses -- Diana, Princess of Wales, 1961-1997